PENGARUH KETERAMPILAN KEWIRAUSAHAAN DAN PERSEPSI PELUANG KERJA TERHADAP MINAT BERWIRAUSAHASISWA SMK NEGERI 1 BANYUDONO - Faizul Aziz (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The research was to find out there is or not: 1) the influence of Entrepreneurship Skill towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono; 2) the influence of Perception on Employment Oppurtunity towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono; 3) the influence of Entrepreneurship Skill and Perception on Employment Oppurtunity towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono. This research used quantitative research with a correlational research design. The population in this research were all students of class XII Automation and Office Administration at SMK Negeri 1 Banyudono which amaount to 71 students. The sample in this research taken with total sampling technique. The data collection technique used questionnaire and documentaion. The data analysis technique used multiple linier regression analysis. The result of research showed that 1) there was a significant positive influence of Entrepreneurship Skill towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono proved tcount > ttable (6,282 > 1,995) with significance (0,00 < 0,05); 2) there was a significant negative influence of Perception on Employment Oppurtunity towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono proved tcount > ttable (-2,287 > -1,995) with significance (0,025 < 0,05); 3) there was a significant positive influence of Entrepreneurship Skill and Perception on Employment Oppurtunity towards Entrepreneurship Interest student at SMK Negeri 1 Banyudono proved tcount > ttable (30,335 > 3,15) with significance (0,00 < 0,05). The regression similarity of  . R Square of 47,2%. Effective contribution of entrepreneurship skill was 38,5% and effective contribution of perception on employment opportunity was 8,7%.